PERAN APARATUR DESA DALAM AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DI DESA ILUTA KECAMATAN BATUDAA - Lantowa, Felmi D.; Yusuf, Fitria Melynsyah; Jusuf, Arena Samsudin (Program Studi Akuntansi, 2022)
Regional autonomy is a new chapter in the administration of a more decentralized form of government. Likewise, the village government is given the authority to be able to carry out village financial management based on accountability and transparent financial management. The purpose of the study was to identify the Role of Village apparatuses in Village Financial Management Accountability in Iluta Village, Batudaa District. The results showed that the role of village officials in the accountability of village financial management in Iluta Village, Batudaa Subdistrict from five indicators based on Permendagri Number 20 of 2018, two indicators are not yet appropriate, namely the administration stage and the reporting stage, the administration stage is still carried out by the Head of the Administration Section due to the lack of understanding of the Village Treasurer in operating a computer, resulting in the reporting of village government budget realization to the Regency level is still often delayed, but the PMD Office still provides an allowance of fourteen days from the specified time so that it does not affect the disbursement of further funds. Thus, it is necessary to increase the capacity quality of knowledge, and expertise of village officials about computers to improve the performance of village officials in village financial management